Attitude And Behaviour Intention Towards Mobile Marketing: Study Of The Malaysian Mobile Market - Yee, Ding Wei (2009)
This paper examines the drivers of consumer acceptance of SMS-based mobile marketing which will henceforth be referred to as M-marketing.